2021
DOI: 10.1177/01945998211015174
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Short‐ and Long‐term Pneumonia Rate With Laryngoplasty for Unilateral Vocal Fold Paralysis

Abstract: Objective To examine the association of laryngoplasty, voice therapy, and pneumonia rate in patients with unilateral vocal fold paralysis (UVFP). Study Design Population-based retrospective cohort study. Setting Data were collected from the LHID2000 (Longitudinal Health Insurance Database 2000), containing the information of 1 million randomly selected patients in Taiwan. Methods In the LHID2000, we identified 439 patients having new diagnoses of UVFP from 1997 to 2013. We grouped the aforementioned patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Two recent studies set their primary outcome measure as the incidence of pneumonia following UVFP 3,4 . Barnes et al isolated a retrospective cohort of cardiothoracic patients who suffered acute UVFP and evaluated whether IL impacted pneumonia rates 6 months following surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies set their primary outcome measure as the incidence of pneumonia following UVFP 3,4 . Barnes et al isolated a retrospective cohort of cardiothoracic patients who suffered acute UVFP and evaluated whether IL impacted pneumonia rates 6 months following surgery.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, they separated injuries into different etiologies and found that patients with high vagal injury had worse initial FOIS scores and were less likely to have an improvement in Two recent studies set their primary outcome measure as the incidence of pneumonia following UVFP. 3,4 Barnes et al isolated a retrospective cohort of cardiothoracic patients who suffered acute UVFP and evaluated whether IL impacted pneumonia rates 6 months following surgery. A control group was included, as 57 of their 92 patients (62%) declined IL.…”
Section: Literature Reviewmentioning
confidence: 99%